Farmers Perception Regarding Climate Change and Crop Production, Especially for Wheat in Dinajpur District (Journal of Environmental Science and Natural Resources, 2013)
An attempt was made to depict the valuable experience of farmers about climate change, environment and agricultural production, particularly wheat by conducting an opinion survey among 50 years and above aged farmers and agricultural workers in selected mauzas of Dinajpur district. Three hundred thirteen (313) respondents were interviewed in the survey. All the respondents opined regarding climate change in Dinajpur district over time. All of them opined that crop land, crop cultivation and crop yield were affected due to climatic change and changing of climate might pose a big and devastating threat to the production of wheat. Besides, the three case studies were accomplished to explore new ideas about climate change and the behavior of nature and human culture. They had also similar types of experience about climate change.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14804 J. Environ. Sci. & Natural Resources, 5(2): 129-136 2012